CYTOTOXIC ACTIVITY OF ACIDIC RIBOSOME INACTIVATING PROTEINS MIRABILIS JALAPA L. (RIP MJ-C) NANOPARTICLE FORMULATED WITH LOW-CHAIN CHITOSAN AND LOW-METHYLATED PECTIN - Kristiani, Monica; Sismindari,; Martien, Ronny; Ismail, Hilda; Yuswanto, Agustinus (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: This study aimed to formulate acidic ribosome inactivating protein isolated from Mirabilis jalapa L. (RIP MJ-C) nanoparticle, using low chains chitosan and low methylated pectin, and to evaluate its cytotoxic activity against T47D breast cancer cell line. Methods: RIP MJ-C was isolated from Mirabilis jalapa L leaves using ion exchange chromatography method, and its presence was tested using super coiled double-stranded deoxyribonucleic acid (DNA) cleavage activity. The nanoparticle of RIP MJ-C was formulated using low chains chitosan and low methylated pectin. The optimum formula was characterised using transmission electron microscope (TEM) and particle size analyzer. The cytotoxic activity of the nanoparticle against T47D breast cancer cell-lines was assessed using MTT assay. Results: The optimum formula was obtained at the combination of 0.06% low chain chitosan and 0.02% low methylated pectin. It was revealed that the nanoparticles have a particle size of 54.43±10.14 nm, polydispersity index of 0.514±0.10, and zeta potential of+93.59±6.90 mV. The cytotoxic activity test showed that RIP MJ-C nanoparticles conjugated with anti-EpCAM 9C4 have the highest cell death percentage of 43.20% compared to unformulated RIP MJ-C. Conclusion: It was concluded that the RIP MJ-C nanoparticle conjugated with an anti-EpCAM antibody could enhance the cytotoxicity of RIP MJ-C against T47D breast cancer cell-lines.